Efecto del abono biol en el rendimiento y valor nutricional de las praderas naturales en la finca LUDPI del cantón Gonzanamá, provincia de Loja - Ludeña Piedra, Isaac Alexander (2023)
The present research aimed to demonstrate the effect of biol organic fertilizer on the chemical characteristics of soil and on the nutritional values of natural grasslands in the LUDPI farm of the Gonzanamá canton, province of Loja. An experimental design of completely random blocks was used, one hectare was obtained, dividing it into three equal blocks, each block had two divisions, one control and the other one for treatment with three repetitions, the same was carried out in two phases: field and laboratory. In the botanical composition in the three blocks the presence of the following species among grasses and legumes was obtained: grass (Cynodon dactylon), kikuyo (Pennisetum clandestinum), white clover (Trifolium repens), brush (Cuphea racemosa (L.f) Spreng), bull grass (Cuphea racemosa (L.f) Spreng) and cosa cosa (Cuphea ciliata Ruiz & Pav). There were the best results in terms of plant height for, bull grass (Cuphea racemosa (L.f) Spreng) (P≤0.05), before fertilization it was 19.33 cm and then fertilized 42.77 cm. In the number of leaves there was no significance for any forage species. Regarding the nutritional values, significance was obtained for non-nitrogenous elements (NES) (P=0.004) and not significant for dry matter with (P=0.3); protein with (P=0.45); fat with (P=0.29), ash with (P=0.13) and fiber with (P=0.32). There were no significant results in terms of soil chemical characteristics or forage biomass. It was concluded that the evaluation of biol fertilizer on nutritional value did not have a significant effect, as well as on forage or biomass yield.